Content Gradation OF Sundanese Textbooks for Junior High School and Senior High School (Review Of Facts, Concepts, Principles, and Procedures in The Field of Sundanese Language Study in 2013 Local Content Curriculum Revised 2017) - Dingding Haerudin; Dedi Koswara; Amanda Puspanditaning Sejati (STKIP Singkawang, 2021)
The main reason for conducting this research is that Sundanese textbooks do not describe the material gradation standards according to the needs and background of students at each level of Education, in addition to not presenting a systematic material structure. In connection with the reason above, the purpose of this study is to examine the gradations and structure of the material contained in the Sundanese textbook for Junior High School/MTs and Senior High School/Vocational/MA students. The method used in this research is the description method. While the data collection technique used in this research is library research techniques. The technique is used to describe data based on gradations and structure of subject presented in Sundanese textbooks based on education levels. The data processed in this study is Sundanese language learning materials including 1) literary forms of poetry: poetry, circumcision, wawacan, satire, pupujian, sawer, and kawih; 2) literary forms of prose: fairy tales, short story, novels, puppet story, and drama; 3) non-literary texts: speeches, writers, letters, reports, debates, interviews, and reports reading. As for, the source of the data is Sundanese textbooks for Junior High School/MTs and Senior High School/Vocational/MA students based on the 2013 Local Content Curriculum Revised 2017. The finding of this study is that the composition of Sundanese textbook material for Junior High School/MTs and Senior High School/Vocational/MA students in accordance with the 2013 Local Content Curriculum Revised 2017, nevertheless, not paying attention to the gradation of the material. Things that unintentionally missing from the authors are 1) gradation of writing indicators from competencies achievement or learning objectives, 2) scope of material presentation and depth of material, and 3) variations of operational verbs on the writing tasks. This research can be used as a consideration in compiling the material presented in the textbook, so that the content presented ca be in accordance with students' needs and background based on their level of education.